Early dam builders in Britain - Binnie, G. M. (Thomas Telford, 1987)
An account of the early days of water engineering, this volume traces the development of dam building in Britain from Roman times to the Victorian period. The author's research provides information for both the layman and the professional engineer.
Keywords: Dams -- Great Britain -- Design and construction.; elektronické knihy; electronic books